DINAMIKA RESILIENSI PADA REMAJA PUTRI YANG MENGALAMI KEHAMILAN TIDAK DIRENCANAKAN - Ni Putu Diah Ananda Fajar (PT. Hasba Edukasi Mandiri, 2026)
Adolescent girls with unplanned pregnancies have low mental health potential. Research was conducted to determine the dynamics and description of resilience in adolescent girls with unplanned pregnancies. The research method uses a literature review that is compiled by reviewing narrative literature using 8 literatures obtained through google scholar. The inclusion criteria in the preparation of this literature review are literature with the topic of resilience in adolescent girls (10-22 years) with a background of having experienced an unplanned pregnancy. So this study shows the results that the description of resilience in adolescent girls with unplanned pregnancies is reviewed from seven aspects of resilience, namely emotion regulation, empathy, reaching out, impulse control, self-efficacy, optimism, and problem cause analysis. In achieving resilience, adolescents go through several phases, namely succumbing, survival, recovery, and thriving. Resilience in adolescents is also supported by several factors, namely internal factors (within self) and external factors (outside self).